Trends in Hospitalizations for Peptic Ulcer Disease, United States, 1998–2005 - Lydia B. Feinstein; Robert C. Holman; Krista L. Yorita Christensen; Claudia A. Steiner; David L. Swerdlow (Emerging Infectious Diseases, 2010)
Infection with Helicobacter pylori increases the risk for peptic ulcer disease (PUD) and its complications. To determine whether hospitalization rates for PUD have declined since antimicrobial drugs to eradicate H. pylori became available, we examined 1998–2005 hospitalization records (using the Nationwide Inpatient Sample) in which the primary discharge diagnosis was PUD. Hospitalizations for which the diagnosis was H. pylori infection were also considered. The age-adjusted hospitalization rate for PUD decreased 21% from 71.1/100,000 population (95% confidence interval [CI] 68.9–73.4) in 1998 to 56.5/100,000 in 2005 (95% CI 54.6–58.3). The hospitalization rate for PUD was highest for adults >65 years of age and was higher for men than for women. The age-adjusted rate was lowest for whites and declined for all racial/ethnic groups, except Hispanics. The age-adjusted H. pylori hospitalization rate also decreased. The decrease in PUD hospitalization rates suggests that the incidence of complications caused by H. pylori infection has declined.